2014
DOI: 10.1103/physrevb.89.075423
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-plane and in-plane actuation effects on atomic-scale friction

Abstract: The influence of out-of-plane and in-plane contact vibrations and temperature on the friction force acting on a sharp tip elastically pulled on a crystal surface is studied using a generalized Prandtl-Tomlinson model. The average friction force is significantly lowered in a frequency range determined by the "washboard" frequency of the stick-slip motion and the viscous damping accompanying the tip motion. An approximately linear relationship between the actuation amplitude and the effective corrugation of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…Furthermore, they showed that the friction force can be resonantly reduced by superimposing torsional oscillation on a cantilever for a low scan velocity. Another aspect of this study has been recently investigated [9,10], and an analytical formula of friction as a function of the excitation amplitude is also introduced at zero temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they showed that the friction force can be resonantly reduced by superimposing torsional oscillation on a cantilever for a low scan velocity. Another aspect of this study has been recently investigated [9,10], and an analytical formula of friction as a function of the excitation amplitude is also introduced at zero temperature.…”
Section: Introductionmentioning
confidence: 99%
“…At the macro scale, gears and bearings and liquid lubricants can reduce friction, but these methods may fail at the micro-or nanoscale [5]. Ultrasonic excitation has been proven to reduce friction at the macroscale [6][7][8][9][10] and the nanoscale [5,[11][12][13][14][15][16][17][18][19][20]. However, the studies on the ultrasonic vibration at the nanoscale are still insufficient [6].…”
Section: Introductionmentioning
confidence: 99%
“…Under frequencies of 319 MHz, 285 Hz, and 250 Hz, friction forces of the diamond tip reach the lowest. Fajardo [20] pointed out that, when vs/a ≤ f ≤ fp/ϒ , friction decreases under external vibration, where f is the vibration frequency, vs is the support velocity, a is the spatial periodicity, and fp is the resonance frequency. ϒ = γ/(2πfp), where γ is a microscopic friction coefficient describing the coupling with the phonon and the possible electron oscillations in the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Guo et al [19] discussed the control of vibration to reduce friction based on a 1D model imitating the friction force microscope (FFM) tip moving on a substrate. Fajardo et al [20] indicated that, under out-of-plane and in-plane contact vibrations, average friction forces were both significantly lowered in a frequency range determined by the "washboard" frequency of the stick-slip motion and the viscous damping accompanying the tip motion. However, Roth et al [21] studied the influence of lateral vibrations on the stick-slip motion by atomic force microscopy (AFM) measurements on an NaCl (001) surface.…”
Section: Introductionmentioning
confidence: 99%